Invited Lecture 7: The Influence of Electromagnetic Pollution on Living Organisms - Nasrin Moazami (Wolters Kluwer Medknow Publications, 2020)
Brief Biosketch Nasrin Moazami is an Iranian medical microbiologist and biotechnologist. She was awarded a PhD in 1976, from the Faculty of Medicine at Laval University, Canada. Professor Moazami is the pioneer of biotechnology and microalgae-based fuels in Iran. In 2016 Professor Moazami was appointed as a member of the Scientific Board of the International Basic Sciences Program (IBSP) of UNESCO. She is the founder of the Persian Type Culture Collection (PTCC) and the MIRCEN International Network since 1992. She has received the 'Chevalier de I'Orde des Palmes Academiques' for her outstanding professional research. The professor is the author of 5 books. Electromagnetic fields are present everywhere in our environment but are invisible to the human eye. Electric fields are produced by the local build-up of electric charges in the atmosphere associated with thunderstorms. The earth's magnetic field causes a compass needle to orient in a North-South direction and is used by birds and fish for navigation. Electromagnetic fields and/or electromagnetic radiation, as electromagnetic pollution, affect various elements of the environment. Among the elements of that environment, all living organisms should be placed in the first position. The genesis and evolution of life on Earth took place under the natural electromagnetic fields action described for the first time by Schumann, resulted that, the complex processes between nucleotides in DNA and RNA, as well as DNA sequences, are influenced by EMF in the extremely low frequency (ELF) field. The main structural elements of the cell, namely the cell membrane, nucleus and cytoplasm, form a complex electrochemical system. The kinetics and mechanism of biochemical oxide-reduction (redox) reactions that take place in the cytoplasmic volume and at the interface between the cell membrane and the cytoplasm are determined by the EF electric fields acting on them. Under these conditions, EF of anthropogenic origin, by modifying the natural polarization distributions, of the membrane potentials, can disturb the natural development of biochemical processes, so they can be considered a pollutant factor (the environment electromagnetic pollution. EMF produces both in vivo and in vitro effects on most biological systems. In this context, it is noted that eukaryotic microorganism stimulation (algae, yeasts, moulds) and prokaryotes in the electromagnetic field can be an efficient process in their Bioprocess pathway.